Congenitally bicuspid aortic valves. Clinicogenetic study of 41 families. Issue 12 (December 1978) - Emanuel, R; Withers, R; O'Brien, K; Ross, P; Feizi, O
Abstract : The families of 41 patients with surgically proved isolated bicuspid aortic valves were examined. There were 275 first degree relatives of whom 220 were living, and 188 (85.5%) of these were examined. Seven first degree relatives were found to have aortic valve disease, and in a further 11 there was 'doubtful' evidence of bicuspid aortic valves. In 6 families there was more than 1 affected member and in an additional 7 families there was 1 or more 'doubtful' first degree relative. The minimum family incidence was therefore 14.6 per cent, or 31.7 per cent if 'doubtful' cases were included. The inheritance is most probably multifactorial, but occasionally the condition may occur as an autosomal dominant. The difficulties of diagnosing bicuspid aortic valves before the development of obstruction of left ventricular outflow were encountered and are discussed. The association of a bicuspid aortic valve with asymmetric septal hypertrophy, hypertrophic cardiomyopathy, and Marfan's syndrome was also noted.